The Application of Umar Bin Khattab's Servant Leadership Ethics in Educational Institution Management - Safinatun Najah, Aninda Tri; Putri Anisa, Firdha Aulia; Pramitha, Devi (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study examines leadership in Islam, emphasizing values of ethics, integrity, justice, and responsibility as the main foundation for achieving performance and success in educational institutions. The purpose of this research is to explore the application of Umar bin Khattab's servant leadership ethics in the management of educational institutions in Indonesia. The research method used is library research, where data are obtained from relevant primary and secondary literature, then analyzed using content analysis and descriptive techniques. The results of the study show that the principles of servant leadership, such as simplicity, justice, and public service, when applied in the educational context, can create an inclusive learning environment focused on the well-being of all involved parties. Implementation strategies, including listening, empathy, healing, awareness, persuasion, conceptualization, and foresight, have proven effective in building ethical and service-oriented leadership. Thus, the application of Umar bin Khattab's servant leadership ethics in educational institutions not only produces individuals who excel academically but also possess high integrity and deep social concern.